Nuclear-radiation-resistant halogen-free low-smoke flame-retardant polyolefin irradiation sheath material and preparation method thereof
Through rational preparation and segmented production of nuclear radiation-resistant halogen-free low-smoke flame-retardant polyolefin radiation sheath material is solved, and the problems of material embrittlement and performance degradation under nuclear radiation are achieved, and the advantages are achieved in a high-dose radiation environment Flame retardant performance and bending resistance meet the multiple performance requirements of nuclear power plant cables.
Patent Information
- Application Number
- CN202411549811.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-10
AI Technical Summary
Nuclear radiation will cause molecular chain breakage and cross-linking reactions of polymer composite materials, causing the material to become embrittled, physical and mechanical properties and flame retardant properties to decrease, and in nuclear power plant environments, it is necessary to have heat resistance, radiation resistance and LOCA resistance. , existing materials are difficult to meet these multiple requirements.
Using a nuclear radiation-resistant halogen-free low smoke flame-retardant polyolefin radiation sheath material, through reasonable preparation of polar copolymers, elastomers, polyethylenes, graft materials, flame retardant, flame retardant synergist, and anti-oxygen The agent and lubricant are produced by segmented processes to ensure uniform dispersion of each component and improve the radiation resistance and processing properties of the material.
The material still maintains excellent flame retardant properties and anti-bending cracking properties under high doses of nuclear radiation, meets the requirements of 60Co-γ ray cumulative dose of 1350kGy, and meets the low-toxic and RoHS2.0 environmental protection standards, and is suitable for long-term high-temperature aging and nuclear Radiation environment.
Smart Images

Figure BDA0005114772500000011 
Figure BDA0005114772500000031 
Figure BDA0005114772500000041
Abstract
Description
Technical Field
[0001] The invention relates to a nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin irradiation sheath material and a preparation method thereof, belonging to the technical field of cables. Background Art
[0002] Nuclear radiation can cause the molecular chains of polymer composite materials to break and cross-link. This cross-linking reaction will make the composite material harder and more brittle, lose some elasticity, and crack after bending. At the same time, the molecular chain breaks and produces free radicals, which trigger free radical reactions, resulting in a decrease in the physical and mechanical properties, flame retardant properties, electrical properties and other comprehensive properties of the composite material, which reduces the service life of the material. Therefore, when using in a nuclear radiation environment, it is necessary to comprehensively consider the radiation resistance of the composite material and the requirements of the specific application.
[0003] The materials used in nuclear power plant cables must have environmental resistance in their working environment, that is, heat resistance, radiation resistance, and LOCA resistance. (1) Heat resistance. Since nuclear power plant cables often work in high temperature environments, they need to have long-term heat resistance. Polymers that meet the heat resistance requirements should be selected, and the cables should have a service life of more than 60 years. (2) Radiation resistance (mild environment, harsh environment). When nuclear power plant cables are exposed to a large amount of radiation, the insulation and sheath materials will become brittle and the mechanical properties will deteriorate. Therefore, as the insulation and sheath materials used in nuclear power plant cables, they must have excellent radiation resistance. (3) LOCA resistance. In nuclear power plants, loss of coolant accidents (abbreviated as LOCA) and high energy line breaks (abbreviated as HELB) are generally referred to as LOCA. When LOCA / HELB occurs, the cables will be impacted by high-temperature and high-pressure steam and corrosive chemicals, and will be exposed to higher radiation than in normal operation. Therefore, nuclear power plant cables should be resistant to LOCA.
[0004] In addition, the sheath material of the cable used in nuclear power plants must be flame-retardant, low-smoke, low-toxic, and non-corrosive cable materials, such as thermoplastic or cross-linked halogen-free, low-smoke, flame-retardant polyolefin materials, to meet special nuclear safety requirements. Halogen-free, low-smoke, flame-retardant cables have low smoke production and will not release any harmful substances in the event of a fire. Their flame-retardant components can effectively play a flame-retardant role and will not make the cable a channel for the spread of flames. Summary of the invention
[0005] The first object of the present invention is to provide a nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin irradiation sheath material. The instrument, control and power cables prepared by the material can maintain excellent flame retardant properties after being irradiated under conventional working conditions (resistant to 60Co-γ ray cumulative dose of 500kGy / room temperature) and accident working conditions (DBA and AG, resistant to 60Co-γ ray cumulative dose of 850kGy / room temperature), with a total cumulative dose of 1350kGy, and the cable will not crack even if bent at 20 times the outer diameter.
[0006] The second object of the present invention is to provide a nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin radiation sheath material, which is compounded with commonly used flame retardants, flame retardant synergists, antioxidants, etc., and can also achieve the purpose of nuclear radiation resistance, and meets environmental protection requirements such as low toxicity and RoHS2.0.
[0007] The third object of the present invention is to provide a method for preparing a nuclear radiation resistant, halogen-free, low-smoke, flame-retardant polyolefin irradiation sheath material, which adopts a segmented process to ensure that various additives can be evenly dispersed to avoid aggregation problems that lead to the existence of local defects.
[0008] To achieve the above object, the present invention adopts the following technical scheme: a nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin irradiation sheath material, the raw material components and the weight proportions of each component are respectively:
[0009]
[0010] in,
[0011] The polar copolymer is one or a mixture of two of ethylene-vinyl acetate copolymer, ethylene-butyl acrylate copolymer and ethylene-ethyl acrylate copolymer;
[0012] More preferably, the polar copolymer is an ethylene-vinyl acetate copolymer and an ethylene-butyl acrylate copolymer in a mass ratio of (1-2): (1-2), wherein the vinyl acetate content of the ethylene-vinyl acetate copolymer is 50%, and the butyl acrylate content of the ethylene-butyl acrylate copolymer is 27%.
[0013] ——The applicant has found through research that ethylene-butyl acrylate copolymer still has excellent low-temperature resistance at -35°C, and the polarity of ethylene-butyl acrylate copolymer is about 1 times higher than that of ethylene-vinyl acetate copolymer with the same proportion of monomer acid content. Therefore, according to the principle of "like dissolves like", its ability to resist corrosion by non-polar oil (902# oil) is higher. However, the flame retardant performance of ethylene-butyl acrylate copolymer is significantly lower than that of ethylene-butyl acrylate copolymer, and its combustion heat release is large.
[0014] The elastomer is one of ethylene-butene copolymer elastomer, ethylene-octene copolymer elastomer and EPDM rubber, or a mixture of two of them;
[0015] Further preferably, the elastomer is a mixture of ethylene-octene copolymer elastomer and ethylene propylene diene monomer rubber in a mass ratio of 1:1, which mainly plays the role of improving low-temperature stretching at -35°C. The filling capacity of ethylene-octene copolymer elastomer is better than that of ethylene propylene diene monomer rubber, but the low-temperature resistance of ethylene propylene diene monomer rubber is better than that of ethylene-octene copolymer elastomer. The two can be used together to play a complementary role.
[0016] The polyethylene is one or a mixture of two of low-density polyethylene, linear low-density polyethylene, bimodal polyethylene, medium-density polyethylene, and high-density polyethylene;
[0017] Further preferably, the polyethylene is medium-density polyethylene, which has better oil resistance in the environment of high-temperature immersion in 902# test oil. This is mainly because medium-density polyethylene has high density, high crystallinity, and high melting point. Under high temperature conditions, small molecule oil agents are not easy to penetrate into the polyethylene molecules, making it show excellent oil resistance. High-density polyethylene has a higher density, higher crystallinity and melting point, and better oil resistance. Compared with medium-density polyethylene, high-density polyethylene has a slightly lower filling capacity and slightly lower interfacial compatibility with polar copolymers and elastomers. Even if a small amount is added, it will still cause a large decrease in mechanical properties.
[0018] The grafted material is one of maleic anhydride grafted polyethylene, maleic anhydride grafted elastomer, and maleic anhydride grafted polar copolymer;
[0019] Further preferably, the grafted material is a maleic anhydride grafted elastomer (for example, the carrier is ethylene-octene copolymer elastomer POE-g-MAH), the maleic anhydride grafting rate is 0.9%, and the melt index is 1.5g / 10min. Its main function is to act as a "bridge" connecting the high molecular polymer and the filler, increasing the bonding force of the phase interface, thereby improving the tensile properties of the material. In addition, because its carrier is an elastomer, it has better low temperature resistance.
[0020] The flame retardant is a mixture of two of aluminum hydroxide, magnesium hydroxide and antimony trioxide;
[0021] More preferably, the flame retardant is a mixture of chemically produced magnesium hydroxide and antimony trioxide in a mass ratio of (2-4):1.
[0022] ——The applicant has found through research that the chemical magnesium hydroxide has a dehydration rate of only 0.1% after continuous aging for 2880 hours (i.e. 120 days) at a high temperature of 155°C, which is significantly better than aluminum hydroxide (dehydration rate of 1.8%). This conclusion shows that the chemical magnesium hydroxide has a strong ability to resist long-term high-temperature dehydration. It can still maintain excellent flame retardant properties after long-term high-temperature accelerated aging when used in nuclear-grade cable materials. Antimony trioxide not only plays a role in gas phase flame retardancy, but is also a material with excellent radiation resistance. It not only inhibits the cross-linking reaction of the material in the nuclear radiation environment and reduces the impact of material degradation, but also can improve the problem of poor carbonization of the material after irradiation by an electron accelerator.
[0023] The flame retardant synergist is at least two of zinc borate, nanoclay, carbon nanotubes, glass powder, and hydrotalcite;
[0024] More preferably, the flame retardant synergist is a mixture of carbon nanotubes, borate glass powder and hydrotalcite in a mass ratio of 1:(1-2):(1-3).
[0025] ——The applicant has found through research that carbon nanotubes will show a larger specific surface area and pore volume after being exposed to nuclear radiation, the surface functional groups will be rearranged and reconstructed, and the surface free radical content will be reduced, which can not only effectively inhibit the generation and propagation of microcracks in the interface area, but also absorb the free radicals generated after nuclear radiation, thereby delaying the degradation rate of the composite material in a nuclear radiation environment. In addition to acting as a binder for repairing carbon layer cracks, the boron element of borate glass powder can absorb neutrons generated by nuclear radiation, thereby reducing the impact of nuclear radiation. Hydrotalcite contains a large amount of structural water and carbonate. When heated, these water and carbon dioxide will be released, thereby achieving a flame retardant effect. At the same time, nano hydrotalcite will be transformed into a porous solid base with a high specific surface area. This solid base can strongly adsorb smoke and toxic acid gases generated by combustion. In addition, its metal ions have a strong adsorption capacity, which can absorb radioactive cobalt ions and iodine ions, and has an anti-nuclear radiation effect.
[0026] The lubricant is one or a mixture of two of polyethylene wax, organic fluoride, zinc stearate and ethylene bis stearamide.
[0027] Further preferably, the lubricant is a mixture of organic fluoride and ethylene bis stearamide in a mass ratio of 1: (1-2), wherein PPA can greatly improve the fluidity of the material, has a very good lubricating effect on high-viscosity resins, reduces or eliminates die head precipitates, eliminates melt fracture, improves surface quality, and does not affect other properties. EBS has both internal and external lubrication effects, which can improve the fluidity and demoulding properties of the material during plasticization.
[0028] The antioxidant is a mixture of at least two of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol, tris[2,4-di-tert-butylphenyl]phosphite, dilauryl thiodipropionate, distearyl thiodipropionate, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, pentaerythritol tetrakis(3-laurylthiopropionate) and 4,4'-thiobis(6-tert-butyl-3-methylphenol).
[0029] More preferably, the antioxidant is a mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], dilauryl thiodipropionate, pentaerythritol tetrakis(3-laurylthiopropionate), and 4,4'-thiobis(6-tert-butyl-3-methylphenol) in a mass ratio of (1-2):(1-3):1:(1-4).
[0030] ——The applicant has found through research that tris[2,4-di-tert-butylphenyl]phosphite and distearyl thiodipropionate have poor compatibility with the substrate and are prone to frosting. Pentaerythritol tetra(3-laurylthiopropionate) is a high-temperature resistant long-acting antioxidant, which is beneficial for polyolefin materials to resist high-temperature aging at 180°C and 165°C. In addition, sulfur-containing antioxidants will inhibit the cross-linking reaction of polyolefin materials in a radiation environment to a certain extent, and the sulfur element can absorb part of the nuclear radiation and reduce the penetration of nuclear radiation rays.
[0031] The dispersant is a silane coupling agent.
[0032] The preparation method of the above-mentioned radiation-resistant, halogen-free, low-smoke, flame-retardant polyolefin irradiation sheath material comprises the following steps:
[0033] Step 1: Feed the flame retardant synergist, antioxidant and a part of the polar copolymer into a forced feeding cone using a loss-in-weight feeding scale according to the mass fraction, and then pass through a twin-screw compounding granulator, hot cutting of the die surface, air cooling and packaging to obtain material B. Among them, the required polar copolymer accounts for (40-45)% of the total amount of the polar copolymer;
[0034] The temperature of the first to seventh zones of the twin-screw extruder is set to 145-150°C for the first to third zones, 135-140°C for the fourth to seventh zones, and 130-135°C for the die.
[0035] ——The applicant has found through research that the polar copolymer is selected as a carrier, and the flame retardant synergist and antioxidant are blended and granulated to obtain material B, and then material B is used for two-stage mixing. Compared with directly adding the flame retardant synergist and antioxidant to the mixing, the former has better dispersion in the entire polyolefin material. The two are observed by film blowing using a Haake rheometer. When adding material B, the agglomeration problem of the flame retardant synergist and antioxidant is significantly improved, and the dispersion is more uniform.
[0036] In step 1, 1) the required polar copolymer generally accounts for (40-45)% of the total polar copolymer. This is mainly because the carbon nanotubes and hydrotalcite in the flame retardant synergist are both nanometer-sized and have a certain polarity on the surface. If added directly, they are prone to agglomeration problems. The amount of antioxidant used is small, and it is not easy to disperse evenly if added directly. Therefore, the flame retardant and antioxidant are made into B material for addition, which is easier to disperse in the entire system. 2) Polar powder materials and polar resins have strong intermolecular forces and better compatibility, especially antioxidants with small molecular weights, which are not easy to migrate from polar resins, avoiding the occurrence of "blooming" problems.
[0037] Step 2: Weigh the remaining raw materials and material B according to their mass fractions and put them into the internal mixer for mixing. When the material temperature reaches 160-165°C, discharge the material, pass through the double-cone feeding system to the twin-screw extruder, and finally enter the single-screw extrusion granulation, air-cooling and packaging to obtain the finished material.
[0038] The double-cone feeding temperature is set to 105-110°C, the temperature of zones 1 to 7 of the twin-screw extruder is set to 90-100°C from zone 1 to zone 2, and 80-90°C from zone 3 to zone 7; the temperature of the single-screw extruder is set to 110-115°C from zone 1, 120-125°C from zone 2, 125-130°C from zone 3, 130-135°C from the die head, and 135-140°C from the hot cutting die surface.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The raw materials used in the present invention are simple, widely available, and reasonably proportioned. The synergistic effect between the components is significant, so good processing performance, excellent physical and chemical properties, and nuclear radiation resistance can be obtained. The two-stage production process can fully ensure the dispersion uniformity of the component materials and meet the requirements of industrial mass production.
[0041] The invention introduces a nuclear radiation-resistant flame retardant, a flame retardant synergist and an antioxidant into a polyolefin substrate, so that the polyolefin material can still maintain excellent flame retardancy and anti-bending cracking performance after long-term high-temperature aging and damage caused by nuclear radiation. DETAILED DESCRIPTION
[0042] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0043] The raw materials in the examples are all commercially available.
[0044] The raw material information of each implementation is shown in the following table.
[0045]
[0046] In each example, the composition of the nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin irradiation sheath material is shown in the following table, wherein parts represent parts by weight.
[0047]
[0048]
[0049] The preparation methods of the nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin irradiation sheath materials of Examples 1 to 10 and Comparative Examples 1 to 10 are:
[0050] Step 1: Feed the flame retardant synergist, antioxidant and a part of the polar copolymer into a forced feeding cone using a loss-in-weight feeding scale according to the mass proportion, and then pass through a twin-screw compounding granulator, hot cut the die surface, and air-cooled packaging to obtain material B.
[0051] The temperature of the first to seventh zones of the twin-screw extruder is set to 145-150°C for the first to third zones, 135-140°C for the fourth to seventh zones, and 130-135°C for the die.
[0052] Step 2: Weigh the remaining raw materials and material B according to their mass fractions and put them into the internal mixer for mixing. When the material temperature reaches 160-165°C, discharge the material, pass through the double-cone feeding system to the twin-screw extruder, and finally enter the single-screw extrusion granulation, air-cooling and packaging to obtain the finished material.
[0053] The double-cone feeding temperature is set to 105-110°C, the temperature of zones 1 to 7 of the twin-screw extruder is set to 90-100°C from zone 1 to zone 2, and 80-90°C from zone 3 to zone 7; the temperature of the single-screw extruder is set to 110-115°C from zone 1, 120-125°C from zone 2, 125-130°C from zone 3, 130-135°C from the die head, and 135-140°C from the hot cutting die surface.
[0054]
[0055]
[0056]
[0057]
[0058] It can be seen from the test data of Example 1, Example 4 and Comparative Example 1 that the introduction of ethylene-butyl acrylate copolymer EBA has a significant improvement on the low-temperature tensile properties. As the dosage increases, the low-temperature tensile elongation at break increases, but it has a certain reverse effect on the elongation at break and oil resistance.
[0059] The test data of Example 1, Comparative Example 2 and Comparative Example 3 can verify that the mechanical properties of ethylene-octene copolymer elastomer are significantly better, while the -35°C low-temperature tensile strength of EPDM rubber is better. The use of the two together can play a complementary role.
[0060] It can be verified from the test data of Example 1, Example 7, Example 8 and Comparative Example 7 that the reduction in the amount of polar copolymer leads to a significant decrease in high temperature (180°C, 165°C) aging resistance, which indicates that the higher the polarity of the polyolefin resin, the better the thermal oxidation aging resistance. The reduction in the amount of polyethylene leads to a significant decrease in oil resistance, which indicates that polyethylene has better oil resistance, mainly because polyethylene is a crystalline polymer with high crystallinity, long molecular chain, and a more stable crystal structure, thereby improving the oil resistance of the material. The polar copolymer has high powder filling capacity and good elongation at break, and polyethylene has high crystallinity and high tensile strength. The two can complement each other when used together.
[0061] It can be verified from the test data of Example 1, Example 9 and Comparative Example 8 that the amount of grafting material has a certain influence on the low-temperature performance. On the one hand, because the carrier is selected as an elastomer, the more grafting material is used, the greater the proportion of elastomer is, and the better the low temperature is. On the other hand, the more grafting material is used, the stronger the "bridge" connecting the high molecular polymer and the filler is, the greater the bonding force of the phase interface will be, and the tensile properties of the material will be improved.
[0062] It can be verified from the test data of Example 3, Example 10, Comparative Example 9 and Comparative Example 10 that after increasing the dosage of flame retardant and flame retardant synergist respectively, the flame retardant performance is significantly improved, but the mechanical properties and thermal aging properties are deteriorated. This is mainly because the excessive dosage of flame retardant destroys the continuity and integrity of the polyolefin substrate, thereby causing a decrease in mechanical properties. The particle sizes of carbon nanotubes and hydrotalcite are both nanometer-level. When the dosage is too high, agglomeration problems are likely to occur, which destroys the entire polyolefin system and causes a significant decrease in mechanical properties.
[0063] By comparing the test data of Example 1, Example 3, Comparative Example 4, Comparative Example 5 and Comparative Example 10, it can be verified that the increase in the amount of carbon nanotubes has a relatively large impact on the electrical insulation performance and the thermal oxidation aging performance. This is mainly because the carbon nanotubes have a certain conductivity. At the same time, the carbon nanotubes have very fine particle sizes, which are prone to agglomeration problems (unable to achieve an ideal dispersion state), which will cause stress concentration and lead to a decrease in the heat resistance of the material, but the flame retardant performance has an improvement trend. After removing the hydrotalcite or carbon nanotubes, the cable is irradiated with 60Co-γ rays, and the elongation at break retention rate and flame retardant performance of the sheath material decrease significantly, which shows that the hydrotalcite and carbon nanotubes have certain anti-nuclear radiation performance.
[0064] It can be verified from the test data of Example 1, Example 2 and Comparative Example 6 that the increase in the amount of antimony trioxide has a certain inhibitory effect on irradiation, the degree of crosslinking is significantly reduced, and the loss of antioxidants during irradiation is small, so the thermal aging performance is improved, but due to the low degree of crosslinking, the oil resistance is significantly reduced. At the same time, antimony trioxide has a greater impact on flame retardancy, and the flame retardancy is significantly improved when the amount is reduced. However, after 60Co-γ ray radiation, the flame retardancy, elongation at break retention rate, and bending crack resistance are significantly reduced, which shows that antimony trioxide has a significant inhibitory effect on nuclear radiation degradation to a certain extent. Therefore, the amount of antimony trioxide should be appropriate to avoid excessive use affecting the flame retardancy, or less use causing a decrease in nuclear radiation resistance.
[0065] Comparison of the test data of Example 1, Example 5 and Example 6 shows that the radiation resistance of the material decreases significantly when the amount of sulfur-containing antioxidant used is reduced, which indicates that the sulfur-containing antioxidant has a significant inhibitory effect on nuclear radiation degradation, but the oil resistance is significantly improved. This is mainly because the antioxidant has an inhibitory effect on irradiation. The reduced amount reduces the inhibitory effect, which increases the cross-linking density of the material and makes it difficult for small molecule oil additives to penetrate into the material. In addition, the reduction in the amount of 412S significantly deteriorates the material's resistance to high temperature aging at 180°C and 165°C, but has little effect on the resistance to medium and low temperature aging at 135°C, which indicates that 412S is a high temperature resistant long-acting antioxidant, which does not affect the resistance to medium and low temperature aging at 130°C.
[0066] It can be seen from the test data of the embodiments and comparative examples that the nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin radiation sheathing materials provided by Examples 1 and 9 of the present invention have excellent nuclear radiation resistance, mechanical properties, heat aging resistance, and flame retardant properties.
[0067] The WDZ-HKYJYJGP-0.6 / 1kV 2*0.5 control cable prepared by the nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin sheath material of Examples 1 and 9 of the present invention still has good flame retardant properties after high-temperature aging at 165°C for 21 days and 60Co-γ ray radiation (cumulative dose of 1350kGy / room temperature). The cable remains intact and crack-free after bending, and meets the low toxicity and RoHS2.0 environmental protection requirements.
[0068] By comparing the nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin irradiation sheath materials of the embodiments of the present invention and the comparative examples, it is found that antimony trioxide, carbon nanotubes, hydrotalcite, sulfur-containing antioxidants, etc. all have certain nuclear radiation resistance, and after compound use, the nuclear radiation resistance is better.
[0069] The above embodiments of the present invention are only for explaining the principle and efficacy of the present invention, and are not intended to limit the present invention. Any person familiar with the technology may modify or change the above embodiments without violating the spirit and scope of the present invention. Therefore, all equivalent modifications or changes made by a person with ordinary knowledge in the technical field without departing from the spirit and technical ideas disclosed by the present invention shall be included in the protection scope of the claims of the present invention.
[0070] In this experimental design, some raw materials are not used in the examples. These raw materials can be used in the formula, but the raw materials used in the examples are better, as follows:
[0071] 1) Ethylene-ethyl acrylate copolymer (EEA) among polar copolymers;
[0072] Compared with EVM and EBA, the powder filling capacity of EEA is weaker than that of EVM, and its high temperature resistance is lower than that of EBA. Therefore, after comprehensive comparison, EVM and EBA are selected for compound use.
[0073] 2) Ethylene-octene copolymer elastomer among elastomers;
[0074] Compared with ethylene-butene copolymer elastomer, ethylene-octene copolymer elastomer has better low temperature resistance, its brittle temperature is lower than -76°C, and it can still maintain good toughness and elongation even at lower temperatures.
[0075] 3) Low-density polyethylene, linear low-density polyethylene, bimodal polyethylene, and high-density polyethylene in polyethylene;
[0076] The molecular weight is large, the crystallinity is high, the melting point is high, and the resistance to 902# oil is good. Compared with low-density polyethylene, linear medium-density polyethylene, and bimodal polyethylene, medium-density polyethylene has a higher melting point. However, the high crystallinity has poor powder filling capacity on the one hand, and poor compatibility with polar copolymers on the other hand. Therefore, after comprehensive comparison, medium-density polyethylene is selected.
[0077] 4) Maleic anhydride grafted polyethylene and maleic anhydride grafted polar copolymer in the grafted material;
[0078] Compared with polyethylene and polar copolymers used as grafted material carriers, elastomers used as carriers have better low-temperature resistance.
[0079] 5) Aluminum hydroxide in flame retardants;
[0080] Compared with aluminum hydroxide, magnesium hydroxide has a higher decomposition temperature and better heat stability. Especially in terms of resistance to long-term high-temperature dehydration, aluminum hydroxide is slightly inferior to magnesium hydroxide.
[0081] 6) Zinc borate and nanoclay in flame retardant synergists;
[0082] Compared with borate glass powder, zinc borate is also a boron-containing substance with certain resistance to nuclear radiation, but its melting point is relatively high, exceeding 900°C, so during the combustion process, the carbon layer repairing effect of boric acid is limited; both nanoclay and carbon nanotubes have the function of promoting carbonization, and nanoclay is slightly better than carbon nanotubes, but carbon nanotubes can absorb free radicals produced after nuclear radiation, thereby delaying the degradation rate of composite materials in a nuclear radiation environment.
[0083] 7) Polyethylene wax and zinc stearate in lubricants;
[0084] In this formulation system, the lubricating effect of organic fluoride and polyethylene wax is the same, both are external lubricating effects. The main small molecule additives migrate from the inside of the polymer to the surface, reducing the friction between the polymer and the surface of the processing equipment. However, in addition to the external lubricating effect, organic fluorine is also an anti-dripping agent, which can promote the formation of carbon layer during the combustion of polymers. Compared with zinc stearate, ethylene bis stearamide has both internal and external lubricating effects and has less effect on the tensile strength of the material.
[0085] 8) Antioxidants: tris[2,4-di-tert-butylphenyl]phosphite, distearyl thiodipropionate, and 4,4'-bis(α,α-dimethylbenzyl)diphenylamine.
[0086] When tris[2.4-di-tert-butylphenyl]phosphite and distearyl thiodipropionate are used as auxiliary antioxidants, they are used in combination with pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, which has a good synergistic effect, especially for long-term aging at 135°C. However, they have poor compatibility with polyolefin resins and are easy to migrate to the surface of the material, forming a "blooming problem". 4.4'-bis(α,α-dimethylbenzyl)diphenylamine and pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate can both be used as primary antioxidants, which can effectively improve the aging resistance of the material and extend the service life of the material. However, the market price of 4.4'-bis(α,α-dimethylbenzyl)diphenylamine is 2-3 times higher than that of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.
Claims
1. A nuclear radiation resistant, halogen-free, low-smoke, flame-retardant polyolefin irradiation sheath material, characterized in that The weight parts of the raw material components and each component are respectively: in, The polar copolymer is one or a mixture of two of ethylene-vinyl acetate copolymer EVA, ethylene-butyl acrylate copolymer EBA, and ethylene-ethyl acrylate copolymer EEA; The elastomer is one of ethylene-butene copolymer elastomer, ethylene-octene copolymer elastomer and EPDM rubber or a mixture of two thereof; The polyethylene is one or a mixture of two of low-density polyethylene, linear low-density polyethylene, bimodal polyethylene, medium-density polyethylene, and high-density polyethylene; The grafted material is one of maleic anhydride grafted polyethylene, maleic anhydride grafted elastomer, and maleic anhydride grafted polar copolymer; The flame retardant is a mixture of two of aluminum hydroxide, magnesium hydroxide and antimony trioxide; The flame retardant synergist is at least two of zinc borate, nanoclay, carbon nanotubes, borate glass powder, and hydrotalcite; The lubricant is one or a mixture of two of polyethylene wax, organic fluoride, zinc stearate and ethylene bis stearamide. The antioxidant is a mixture of at least two of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]pentaerythritol, tris[2,4-di-tert-butylphenyl]phosphite, dilauryl thiodipropionate, distearyl thiodipropionate, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine, pentaerythritol tetrakis(3-laurylthiopropionate), and 4,4'-thiobis(6-tert-butyl-3-methylphenol); The dispersant is a silane coupling agent.
2. The nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin irradiation sheath material according to claim 1 is characterized in that the polar The copolymer is a mixture of ethylene-vinyl acetate copolymer and ethylene-butyl acrylate copolymer in a mass ratio of (1-2):(1-2), wherein the vinyl acetate content of the ethylene-vinyl acetate copolymer is 50%, and the butyl acrylate content of the ethylene-butyl acrylate copolymer is 27%.
3. The nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin irradiation sheath material according to claim 1 is characterized in that: The elastomer is a mixture of ethylene-octene copolymer elastomer and ethylene propylene diene monomer rubber in a mass ratio of 1:
1.
4. The nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin irradiation sheath material according to claim 1 is characterized in that The polyethylene is medium-density polyethylene.
5. The nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin irradiation sheath material according to claim 1 is characterized in that The grafted material is a maleic anhydride grafted elastomer, the maleic anhydride grafting rate is 0.9%, and the melt index is 1.5g / 10min.
6. The nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin irradiation sheath material according to claim 1 is characterized in that The flame retardant is a mixture of chemical magnesium hydroxide and antimony trioxide in a mass ratio of (2-4):
1.
7. The nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin irradiation sheath material according to claim 1 is characterized in that The flame retardant synergist is a mixture of carbon nanotubes, borate glass powder and hydrotalcite in a mass ratio of 1:(1-2):(1-3).
8. The nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin irradiation sheath material according to claim 1 is characterized in that The lubricant is a mixture of PPA and EBS in a mass ratio of 1:(1-2).
9. The nuclear radiation resistant halogen-free low-smoke flame-retardant polyolefin irradiation sheath material according to claim 1, characterized in that The antioxidant is a mixture of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], dilauryl thiodipropionate, pentaerythritol tetrakis(3-lauryl thiopropionate), and 4,4'-thiobis(6-tert-butyl-3-methylphenol) in a mass ratio of (1-2):(1-3):1:(1-4).
10. A method for preparing a radiation-resistant, halogen-free, low-smoke, flame-retardant polyolefin irradiation sheath material, characterized in that: First weigh the raw materials according to the formula, and then prepare according to the following steps: Step 1: Mixing and granulating a flame retardant synergist, an antioxidant and a portion of a polar copolymer to obtain material B; wherein the required polar copolymer accounts for (40-45)% of the total amount of the polar copolymer; Step 2: Mix the remaining raw materials with material B; The material is discharged when the mixing temperature reaches 160-165°C, and then subjected to screw extrusion, shearing and stirring, and then extrusion granulation to obtain the finished material.
Citation Information
Cited By
Halogen-free low-smoke flame-retardant polyolefin insulating material for nuclear-grade cable and preparation method of halogen-free low-smoke flame-retardant polyolefin insulating material
CN119875237A
Polyolefin material as well as preparation method and application thereof
CN121537741A